THE EFFECT OF WORK ENVIRONTMENT, SELF EFFICAY, ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON JOB SATISFACTION (Study On PT. Pos Indonesia (Persero) SPP Pos Branch Office Erlangga Semarang) - Nabiila Ronaa Setyadi; Kis Indriyaningrum (SEAN Institute, 2022)
The purpose of this study was to determine the effect of work environment, self-efficacy, organizational citizenship behavior on job satisfaction at PT. Pos Indonesia (Persero) SPP Erlangga Post Office Branch Semarang. The population in this study were employees of PT. Pos Indonesia (Persero) Branch Post Office SPP Erlangga Semarang, totaling 128 employees. The sampling technique used saturated sample so that it involved all the population as many as 128 employees. The data obtained were analyzed using multiple linear regression . The analytical tool used is the IBM SPSS 25 program. The results showed that: (1) Work environment had a positive and significant effect on job satisfaction (2) Self-efficacy had a positive and significant effect on job satisfaction (3) Organizational Citizenship Behavior had a positive and significant effect on job satisfaction